What is it about humanity that we can't give away to intelligent machines? A European perspective. (June 2021) - Coombs, Crispin; Stacey, Patrick; Kawalek, Peter; Simeonova, Boyka; Becker, Joerg; Bergener, Katrin; Carvalho, João Álvaro; Fantinato, Marcelo; Garmann-Johnsen, Niels F.; Grimme, Christian; Stein, Armin; Trautmann, Heike
Highlights: Recent advances in artificial intelligence (AI) have created 'intelligent machines'. The article debates tensions between human freedom and intelligent machine control. AI tensions examined in four contexts: crime and conflict, jobs, attention, and wellbeing. Humans must preserve critique of AI, human involvement in AI decisions, and explainable AI. Presents an agenda for future AI and humanity research. Abstract: One of the most significant recent technological developments concerns the development and implementation of 'intelligent machines' that draw on recent advances in artificial intelligence (AI) and robotics. However, there are growing tensions between human freedoms and machine controls. This article reports the findings of a workshop that investigated the application of the principles of human freedom throughout intelligent machine development and use. Forty IS researchers from ten different countries discussed four contemporary AI and humanity issues and the most relevant IS domain challenges. This article summarizes their experiences and opinions regarding four AI and humanity themes: Crime & conflict, Jobs, Attention, and Wellbeing. The outcomes of the workshop discussions identify three attributes of humanity that need preservation: a critique of the design and application of AI, and the intelligent machines it can create; human involvement in the loop of intelligent machine decision-making processes; and the ability to interpret and explain intelligent machine decision-making processes. The article provides an agenda for future AI and humanity research.